Corynebacterium species isolated from milk samples of dairy cows with mastitis and antibiotic susceptibilities - H. Hüseyin Hadimli; Osman Erganiş; Kürşat Kav; Zafer Sayın (Eurasian Journal of Veterinary Sciences)
In this study, identification of Corynebacterium spp. isolated from dairy cows and detection of theirs antibiotic susceptibililis were aimed. A total of 810 cattle Irom 7 dairy herd has been monitered by CMT, trom a number of 651 samples detected positive by CMT and 64 Corynebacterium spp. were isolated. Of Corynebacterium isolates, 41 (64.06%) were identified as C. amycolatum, 11 (17.18%) C. xerosis. 7 (10.93%) C. minutissimum, 3 (4,68%) C. bovis and 2 (3.12%) C. pseudotuberculosis. While C. pseudotuberculosis isolates were tound to resistant to erythromycin and tincomycin, other Corynebacterium species (C. amycolatum, C, xerosis, C. minutissimum, C. bovis) were differently susceptible to 10 antibacterials agents.